Acute effects of static versus dynamic stretching on isometric peak torque, electromyography, and mechanomyography of the biceps femoris muscle - Herda, T. J.; Cramer, J. T.; Ryan, E. D.; McHugh, M. P.; Stout, J. R. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to examine the acute effects of static versus dynamic stretching on peak torque (PT) and electromyographic (EMG), and mechanomyographic (MMG) amplitude of the biceps femoris muscle (BF) during isometric maximal voluntary contractions of the leg flexors at four different knee joint angles. Fourteen men ((mean ± SD) age, 25 ± 4 years) performed two isometric leg flexion maximal voluntary contractions at knee joint angles of 41°, 61°, 81°, and 101° below full leg extension. EMG (µV) and MMG (m·s-2) signals were recorded from the BF muscle while PT values (Nm) were sampled from an isokinetic dynamometer. The right hamstrings were stretched with either static (stretching time, 9.2 ± 0.4 minutes) or dynamic (9.1± 0.3 minutes) stretching exercises. Four repetitions of three static stretching exercises were held for 30 seconds each, whereas four sets of three dynamic stretching exercises were performed (12-15 repetitions) with each set lasting 30 seconds. PT decreased after the static stretching at 81° (p = 0.019) and 101° (p = 0.001) but not at other angles. PT did not change (p > 0.05) after the dynamic stretching. EMG amplitude remained unchanged after the static stretching (p > 0.05) but increased after the dynamic stretching at 101° (p < 0.001) and 81° (p < 0.001). MMG amplitude increased in response to the static stretching at 101° (p = 0.003), whereas the dynamic stretching increased MMG amplitude at all joint angles (p <= 0.05). These results suggested that the decreases in strength after the static stretching may have been the result of mechanical rather than neural mechanisms for the BF muscle. Overall, an acute bout of dynamic stretching may be less detrimental to muscle strength than static stretching for the hamstrings.